(untitled) (Bangladesh Journal of Pharmacology, 2013)
Aquilaria agallocha Roxb. (Thymelaeceae) heartwood is used in cardiac failure; however, its cardiotonic properties are poorly understood at a pharmacological level. This study investigated methanol extract of A. agallochafor presence of glycosides and its effects on force of contraction, heart rate and coronary flow on rabbit isolated heart. Furthermore, contribution of β1-adrenoceptors and/or L-type Ca2+ channels in A. agallocha-induced cardiac effects was explored. A. agallocha extract, digoxin, verapamil and metoprolol were administered in a retrograde manner. Force of contraction and heart rate were recorded with a force transducer attached to the heart. Coronary flow was measured from collected effluent. The extract induced a significant increase in force of contraction (p<0.001), decrease in heart rate (p<0.05) and coronary flow (p<0.001). Metoprolol (p<0.01) and verapamil (p<0.01) significantly inhibited the plant extract-induced effects. Thus, A. agallocha exhibited cardiotonic effects, most likely via cardiac glycosides, involving ?1-adrenoceptors and L-type Ca2+ channels.